2007
DOI: 10.1097/qad.0b013e3280115402
|View full text |Cite
|
Sign up to set email alerts
|

HIV incidence during a cluster-randomized trial of two strategies providing voluntary counselling and testing at the workplace, Zimbabwe

Abstract: Highly acceptable VCT did not reduce HIV incidence in this predominantly male cohort. HIV incidence was highest in the high uptake VCT arm, lending support to a US trial in which rapid testing appeared to have adverse behavioural consequences in some HIV-negative clients. Careful comparison of outcomes under different counselling and testing strategies is needed to maximize HIV prevention from global scale-up of VCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 25 publications
4
86
1
Order By: Relevance
“…Several HIV and STI incidence studies in Africa have found no population-level impact of VCT (12)(13)(14). Although a critical link to life-prolonging treatment, HIV testing is therefore unlikely to substantially alter the epidemic's course [the potential for domestic violence against women who test positive must also be considered (15)].…”
Section: Hiv Testingmentioning
confidence: 99%
“…Several HIV and STI incidence studies in Africa have found no population-level impact of VCT (12)(13)(14). Although a critical link to life-prolonging treatment, HIV testing is therefore unlikely to substantially alter the epidemic's course [the potential for domestic violence against women who test positive must also be considered (15)].…”
Section: Hiv Testingmentioning
confidence: 99%
“…However, similar effects are not as convincing for the large proportion who test negative. A recent study found increased risk behaviors in HIV negative individuals after undergoing VCT (Sherr et al 2007) while a comparison of two VCT strategies in Zimbabwe found that despite improved acceptability of the trial VCT strategy, risk behaviors continued in individuals testing negative following their diagnosis (Corbett et al 2007). Although there has been a focus on increasing the number of people undergoing HIV testing and counseling, currently less than a quarter of HIV positive individuals in most countries in sub-Saharan Africa are aware of their status (WHO, UNAIDS and UNICEF 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Risk compensation will likely be the bane of vaccines against the virus (Blower and McLean, 1994). While voluntary counselling and testing promotes more condom use among those tested positive for HIV, the majority who test negative have been observed to either maintain risky sexual practices or adopt riskier sexual practices (Corbett et al, 2007;Matovu et al, 2007;Sherr et al, 2007;Weinhardt et al, 1999). Circumcised men have also been observed to have riskier sexual practices than uncircumcised men, likely in response to the awareness of decreased susceptibility to HIV (Bailey et al, 1999).…”
Section: Problems With the Risk Reduction Approach Risk Compensation mentioning
confidence: 99%
“…Antiretroviral therapy is logistically untenable and prohibitively expensive within developing economies, valued at 350 (US) dollars per infected person per year (Creese et al, 2002;Dieffenbach and Fauci, 2011;Walker, 2004). Voluntary counselling and testing, valued at 400 to 500 (US) dollars per infection avoided (Creese et al, 2002), is similarly prohibitive, and its implementation has not been demonstrated to reduce viral prevalence within developing settings (Corbett et al, 2007). Male circumcision appears to be the only risk reduction approach that is both effective and universally applicable, owing to its one-time treatment, its existing prevalence in West Africa and among African Muslims, social acceptability, and its continuous effect with every act of intercourse (Anonymous, 2007;Halperin and Epstein, 2007;Potts et al, 2008;Weiss et al, 2008).…”
Section: Introductionmentioning
confidence: 99%